High prevalence of focal and multi-focal somatic genetic variants in the human brain. Issue 1 (December 2018) - Keogh, Michael; Wei, Wei; Aryaman, Juvid; Walker, Lauren; Ameele, Jelle; Coxhead, Jon; Wilson, Ian; Bashton, Matthew; Beck, Jon; West, John; Chen, Richard; Haudenschild, Christian; et al.
Abstract Somatic mutations during stem cell division are responsible for several cancers. In principle, a similar process could occur during the intense cell proliferation accompanying human brain development, leading to the accumulation of regionally distributed foci of mutations. Using dual platform >5000-fold depth sequencing of 102 genes in 173 adult human brain samples, we detect and validate somatic mutations in 27 of 54 brains. Using a mathematical model of neurodevelopment and approximate Bayesian inference, we predict that macroscopic islands of pathologically mutated neurons are likely to be common in the general population. The detected mutation spectrum also includesDNMT3A andTET2 which are likely to have originated from blood cell lineages. Together, these findings establish developmental mutagenesis as a potential mechanism for neurodegenerative disorders, and provide a novel mechanism for the regional onset and focal pathology in sporadic cases. Similar to cancers, somatic mutations might lead to neurodegenerative diseases. Here, the authors perform ultra-deep sequencing of 102 genes in 173 adult human brains, detect somatic mutations in 54 brains, and develop a mathematical model to estimate the frequency of mutated foci in human brains.